Institutional investors and the credibility of open market repurchases in illiquid markets: evidence from Taiwan. Issue 2 (3rd April 2017) - Cheng, Su-Yin; Hou, Han
ABSTRACT: This paper examines the issue of information advantages via observing the trading behaviour of foreign and domestic institutional investors during the entire execution periods of open market repurchases in Taiwan. A credibility index (foresighted) is constructed to measure the false signal of OMR firms. We find that foreign institutional investors possess an information advantage over domestic institutional investors. They buy companies with higher credibility, whereas domestic institutional investors cannot distinguish between true and false signals, signifying that foreign institutional investors are sophisticated and possess specialised investment experiences. In addition, we find that foreign institutional investors hold high-credibility firms because those firms are linked with higher excess returns than firms with lower credibility.